The analogies between human development and additive manufacture: Expanding the definition of design. Issue 1 (1st January 2019) - Thomas-Seale, L. E. J.; Kirkman-Brown, J. C.; Kanagalingam, S.; Attallah, M. M.; Espino, D. M.; Shepherd, D. E. T.
Abstract: Design techniques represent a huge economic barrier to the progression of Additive Manufacturing (AM) to more industrial applications. The aim of this research is to use biological analogies, taken from human development to offer a new perspective on what the definition of additive design and manufacturing could encompass in the future. Efficient design for additive manufacturing requires increased creativity, something that is currently constrained by the psychological inertia imposed by a history of subtractive manufacturing. The development of the human, i.e. the differentiation and proliferation of cells to form tissues and organs, creates an organism that develops and functions in synergy. This may be considered the epitome of sophisticated AM. In this study, a novel methodology, utilising the Theory of Inventive Problem Solving, was applied to develop bottom-up analogies between the two systems. A detailed biological discussion of human development is presented, offering a vision of how AM could begin to reflect the synergy displayed during the growth of the foetal form. The results propose a series of developments to current design methods and manufacturing systems for AM. In-situ design for AM is projected as an innovative methodology of expanding design freedom to incorporate temporal stimuli and material response through space and scale across the build envelope. Manufacturing technologies under the themes of Hybrid, Suspended, Perfusion and Diffusion Manufacturing are proposed from insight taken from the development of the foetal bones, amniotic fluid, cardiovascular system and the function of the placenta and fast block polyspermy.